Effect of flow rate and freezing on cyanocobalamin recovery using a commercial solid phase extraction cartridge - Lauren Lees; Alison M Bland; Giacomo R DiTullio; Michael G Janech; Peter A Lee (Annals of Marine Science - Peertechz Publications, 2020)
Analysis of vitamin B12 in sea water is laborious, time consuming, and often requires storage of relatively large-volume water samples. Alleviating these major limitations will increase the throughput of samples and, as a consequence, improve our understanding of the distribution and role of vitamin B12 in the oceans. Previous studies have indicated that target analyte recovery is negatively affected at flow rates exceeding 1mLmin-1 using home-made C18 Solid Phase Extraction (SPE) cartridges. In this study, the effect of flow rate on recovery of vitamin B12 was tested across a range of flow rates between 1 and 37mLmin-1 using a commercial SPE cartridge containing surface-modified styrene divinylbenzene. Recovery of vitamin B12 at flow rates up to the maximum rate tested did not statistically differ from 1mLmin-1. A second study was conducted to determine whether storage of the SPE cartridges at -20°C had a negative impact on vitamin B12 recovery. Recovery of vitamin B12 from SPE cartridges stored up to 13days did not differ from unfrozen SPE cartridges. These data suggest that rapid extraction and cold storage of vitamin B12 on commercial SPE cartridges does not negatively affect recovery and offers an economical alternative to field studies.